2017
DOI: 10.1007/s00068-016-0758-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiological evaluation of tube depth and complications of prehospital endotracheal intubation in pediatric trauma: a descriptive study

Abstract: Pediatric endotracheal tube intubation carries a high rate of tube malposition and left lung atelectasis in our experience of pediatric trauma patients, with less than a third of ETTs placed in a safe position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Reporting of airway training was too heterogeneous to support an analysis however. Some studies provided no description of training [19,21,24,26,39,44,45], and some reported pooled data from multiple agencies [3,28,32], whilst others described the studied teams simply as Advanced Life Support and/or Paediatric Advanced Life Support certified [5,20,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reporting of airway training was too heterogeneous to support an analysis however. Some studies provided no description of training [19,21,24,26,39,44,45], and some reported pooled data from multiple agencies [3,28,32], whilst others described the studied teams simply as Advanced Life Support and/or Paediatric Advanced Life Support certified [5,20,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…As there was no inter-group heterogeneity for endobronchial intubation (P = 0.15), the overall pooled estimated was 7% (95% CI 3-12%) ( Table 2). However, Simons and colleagues' study [44] appears to be an outlier (21%, 95% CI 10-37%) as there were exhaustive attempts to determine the endotracheal tube position after arrival in the emergency department. A post hoc sensitivity analysis, excluding Simons and colleagues' study [44], showed that there was a significant inter-group heterogeneity (P < 0.001), with a pooled estimate for physician team decreasing to 0% (95% CI 0-2%).…”
Section: Adverse Eventsmentioning
confidence: 98%
See 1 more Smart Citation
“…Within this context, different techniques should be used to determine where the orotracheal tube should be placed correctly, including a physical examination where epigastric sounds are not heard during ventilation, a chest X-ray to visualize the orotracheal tube, capnography curve, expired CO 2 value of >30 mm Hg, or steam water on the orotracheal tube walls. If any of these signs are altered, the risk of tube misplacement should be considered, which can cause additional complications to esophageal intubation such as bronchoaspiration, esophageal perforation, hypoxia, atelectasis, or even irreversible brain injury caused by hypoxia or death [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…It should be highlighted that trauma is the most observed clinical condition in all papers included in this systematic review, which implies several particular characteristics of this patient type, possibly aggravating scenarios, and has a direct effect on outcomes. In this context, difficulties in airway approach related to physiological factors can be observed owing to injury mechanisms, which cause quick patient deterioration, as well as anatomical factors caused by the trauma itself, such as airway bleeding and anatomical integrity alterations [25,32].…”
Section: Discussionmentioning
confidence: 99%